ANALISIS PENGARUH IKLAN DAN CELEBRITY ENDORSER TERHADAP CITRA MEREK DALAM MENINGKATKAN MINAT BELI PADA PRODUK SEPATU OLAH RAGA ADIDAS (Studi pada Warga Kelurahan Banyumanik,Kecamatan Banyumanik) - Murti, Baskoro Ndaru; Sugiarto Ph, Yohanes (Faculty of Economics and Business Diponegoro University, 2014)
Modern marketing is no longer making a profit achievement of the primary objectives to be achieved , but also how the company is able to instill a strong buying interest to prospective customers . Several attempts to create consumer buying interest is by using advertising as the ingredients and also using celebrity endorser to attract more attention of potential consumers in order to attract consumers and improve the quality of advertising . This study investigated the influence of advertising and celebrity endorser of the brand image increase interest in buying Adidas sneakers at Banyumanik Village , Semarang.Â The number of respondents consisted of 98 people . The data were analyzed using multiple linear regression analysis , Sobel test , test validity and reliability , the classical assumption ,hypothesis testing and analysis of determination ð‘…2 Â . In this study, using primary and secondarydata . Independent variable is advertising and celebrity endorser , intervening variable is thebrand image and the dependent variable is buying interest.Â The results showed that the presence of a positive and significant effect of the variable advertising and celebrity endorser of the brand image and purchase interest and also brand image variables against buying interest . Varabel highest affect buying interest with the results of the regression coefficient value of 0.313 is advertising .